2021
DOI: 10.1177/10547738211033922
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management Micro-Video Health Education Program for Hemodialysis Patients

Abstract: Self-management in hemodialysis patients is critical; however, is generally low. This study aimed to examine the effects of a theory-based micro-video health education program on the improvement of self-management, hemodialysis knowledge, and self-efficacy in hemodialysis patients. A pre-test post-test control group quasi-experimental design was used to recruit 80 hemodialysis patients in a dialysis center. The participants were assigned in a 1:1 ratio to receive routine care or a 3-month micro-video health ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…Another report on heart transplant patients also revealed that using educational software packages had improved adherence to medication therapy 33. Results of another study which used a micro-video health education programme in HD patients showed this method significantly improved self-management and self-efficacy 34. Contrary to the results of the present study, kidney transplant patients in another investigation had about 63.6% treatment adherence with no adherence to medication using a mobile application 35.…”
Section: Discussioncontrasting
confidence: 76%
“…Another report on heart transplant patients also revealed that using educational software packages had improved adherence to medication therapy 33. Results of another study which used a micro-video health education programme in HD patients showed this method significantly improved self-management and self-efficacy 34. Contrary to the results of the present study, kidney transplant patients in another investigation had about 63.6% treatment adherence with no adherence to medication using a mobile application 35.…”
Section: Discussioncontrasting
confidence: 76%
“…The another study examined the effects of the self‐care management video program on patients undergoing hemodialysis and found a statistically significant increase in self‐care knowledge levels in both experimental ( t = −5.27, p < 0.001) and control groups ( t = −2.98, p = 0.007) [20]. Similarly, in their study examining the use of micro‐video training for self‐care management for hemodialysis patients, their reported serious differences in patients' self‐care management according to pre‐test and post‐test results [21]. It was reported for in‐group comparisons that patients in the intervention group showed a significant improvement in the mean scores of self‐care management compared to baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who were admitted to a private hemodialysis center in Kayseri between October and December 2022 were included in the study. The sample group was calculated via G Power based on the sample groups of the studies in the literature [20,21]. The power analysis was done using the G.Power 3.1.9 program and effect size was calculated according to Cohen's f (0.02 low, 0.15 medium, and 0.35 large) and based on a 20% deviation (0.12) from the medium effect size (0.15).…”
Section: Universe and Samplementioning
confidence: 99%
“…However, haemodialysis patients' self-management is not ideal (Ren et al, 2021). It is difficult for haemodialysis patients to maintain lifestyle changes in the long term (Brioni et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Effective self‐management can reduce the incidence of complications and improve patients' quality of life (Noviana & Zahra, 2021). However, haemodialysis patients' self‐management is not ideal (Ren et al, 2021). It is difficult for haemodialysis patients to maintain lifestyle changes in the long term (Brioni et al, 2021).…”
Section: Introductionmentioning
confidence: 99%